Erratum: Datos biográficos de Joseph Quer y Martínez (1695-1764) - Velayos, Guillermo; Medina, Leopoldo; Aedo, Carlos (Botanica Complutensis, 2021)
Errata del artículo: Velayos, G., Medina, L., & Aedo, C. (2020). Datos biográficos de Joseph Quer y Martínez (1695-1764). Botanica Complutensis, 44, 97-99. https://doi.org/10.5209/bocm.73054